2019
DOI: 10.1080/14786419.2019.1678610
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase inhibitory, antibacterial, and antioxidant activities of natural substances from the wood of Derris reticulata Craib

Abstract: Derris reticulata (Leguminosae-Papilionoideae) has been used for the treatment of diabetes in Thai folk remedies. The phytochemical investigation of the wood of D. reticulata revealed the isolation of two new pyranoflavanones, 4-methoxydereticulatin (1) and 2-hydroxy,3ethoxylupinifolin (2), along with five known compounds namely lupinifolin (3), 2,3dihydroxylupinifolin (4), genistein (5), lupeol (6), and -sitosterol (7). Compounds 1-4 were selected for antibacterial assay using broth microdilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Derris reticulata Craib, a climbing medicinal plant used in folk medicine [154], has prenylated flavanones as its main constituents, whose presence has been linked to several pharmacological outcomes, particularly antibacterial activity [154,155]. According to Pulbutr et al [155], the ethanolic extract from stems of D. reticulata was able to inhibit S. mutans DMST 1877 biofilm formation by up to 99.9%, at the highest tested concentration, 750 µg•µL −1 .…”
Section: The Most Promising Medicinal Plant Extracts In the Control Of Oral Biofilmsmentioning
confidence: 99%
“…Derris reticulata Craib, a climbing medicinal plant used in folk medicine [154], has prenylated flavanones as its main constituents, whose presence has been linked to several pharmacological outcomes, particularly antibacterial activity [154,155]. According to Pulbutr et al [155], the ethanolic extract from stems of D. reticulata was able to inhibit S. mutans DMST 1877 biofilm formation by up to 99.9%, at the highest tested concentration, 750 µg•µL −1 .…”
Section: The Most Promising Medicinal Plant Extracts In the Control Of Oral Biofilmsmentioning
confidence: 99%
“…D. reticulata has also been shown to exhibit antioxidant activity. 11,16 It is widely known that inflammatory processes cause an increase in the formation of free radicals. [4][5][6][7] In addition, it has been reported that D. reticulata extract significantly reduces NO production and the expression of several mRNAs and proteins which are proinflammatory cytokines, TNF-α, IL-1 and IL-6, and the enzymes, iNOS and COX-2.…”
Section: In Vivo Anti-inflammatory Activity Of Drementioning
confidence: 99%
“…[11][12] Previous studies have shown that this plant also exerts estrogenic, 13 anticariogenic, 14 antibacterial, antiviral, anti-cancer, -glucosidase inhibitory, antidiabetic, and antioxidant activities. 11,[15][16] Moreover, it has also been shown that ethanol extract from the stem of D. reticulata significantly reduces nitric oxide (NO) production and the mRNA expression of pro-inflammatory cytokines of macrophages, which reveals its anti-inflammatory effect. 17 To the best of our knowledge, no previous pharmacological study has investigated the anti-inflammatory potential of D. reticulata in an animal model.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. Alpinumisoflavone, carpachromene, lupinifolin, oleanolic acid and erythrodiol are both antioxidant and cytotoxic [26,[44][45][46][47][48][49][50][51][52][53]. The other secondary metabolites have only demonstrated cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%